Personnel and industrial psychology - Ghiselli, Edwin E.; Brown, Clarence W. (New York, McGraw-Hill, 1955)
This book shows the need to for using scientific methods and procedures in working with personnel's problems in business, industries and government.
Includes bibliographical index and references
MF23/01/2019
Loans
Keywords: Psychology, Industrial; New York